Indirect treatment comparison of nivolumab versus placebo for the adjuvant treatment of melanoma - Hemstock, M; Kupas, K; Roskell, N; Kotapati, S; Gooden, K; Middleton, MR; Schadendorf, D (Elsevier, 2020)
Introduction Until recently, adjuvant treatment options for stage III and IV resectable melanoma have been limited. Patients were often managed through routine surveillance. The phase III randomised controlled trial (RCT) CheckMate 238 (238) demonstrated the safety and efficacy of nivolumab as an adjuvant treatment for melanoma in patients with stage IIIB/C or IV disease (American Joint Committee on Cancer [AJCC], 7th edition) versus ipilimumab. The study objective was to estimate the relative efficacy, safety and health-related quality of life (HRQoL) between nivolumab and routine surveillance.